Determinants of Foreign Direct Investment and Economic Growth in Regencies/Cities in Bali Province - Sahadewa, I Dewa Gede Nanda; Purbadharmaja, Ida Bagus Putu (CV. Lenggogeni Data Publishing, 2025)
In developing countries such as Indonesia, economic growth faces two main constraints: human resources and capital accumulation. Bali Province, as an integral part of the Republic of Indonesia, exhibits a unique pattern of economic growth compared to other provinces. More specifically, between 2012 and 2024, Bali’s economic growth experienced fluctuations in line with the crises that occurred during this period. This study covers the period 2012–2024 with 117 observation points using panel data. The purpose of this research is to analyze the direct and indirect effects of population size and the Human Development Index (HDI) on foreign direct investment (FDI) and economic growth in the regencies/municipalities of Bali Province, employing path analysis techniques. The results show that both population size and HDI have a positive and significant effect on FDI. Population size has a positive and significant effect on economic growth, HDI also has a positive and significant effect on economic growth, and FDI has a positive and significant effect on economic growth across Bali’s regencies/municipalities. Furthermore, population size and HDI indirectly influence economic growth through FDI. The findings of this study are expected to provide valuable input for the Provincial Government of Bali in formulating strategies to enhance FDI as a driver of sustainable economic growth, by optimizing the role of population, improving human resource quality, promoting a more equitable distribution of investment to non-tourism regions, and regulating investment flows in tourism areas to ensure balanced economic growth across all regencies/municipalities in Bali Province.